Identification of Pre-Spike Network in Patients with Mesial Temporal Lobe Epilepsy - Faizo, Nahla L.; Burianová, Hana; Gray, Marcus; Hocking, Julia; Galloway, Graham; Reutens, David (Frontiers in Neurology, 2014)
Background: Seizures and inter-ictal spikes in mesial temporal lobe epilepsy (MTLE) affect a network of brain regions rather than a single epileptic focus. Simultaneous EEG-fMRI studies have demonstrated a functional network in which hemodynamic changes are time-locked to spikes. However, whether this reflects the propagation of neuronal activity from a focus, or conversely the activation of a network linked to spike generation remains unknown. The functional connectivity changes prior to spikes may provide information about the connectivity changes that lead to the generation of spikes. We used EEG-fMRI to investigate functional connectivity changes immediately prior to the appearance of inter-ictal spikes on EEG in MTLE patients. Methods/principal findings: 15 MTLE patients underwent continuous EEG-fMRI during rest. Spikes were identified on EEG and three 10s epochs were defined relative to spike onset: spike (0s to 10s), pre-spike (-10s to 0s) and rest (-20s to -10s, with no previous spikes in the preceding 45s). Significant spike-related activation in the hippocampus ipsilateral to the seizure focus was found compared to the pre-spike and rest epochs. The peak voxel within the hippocampus ipsilateral to the seizure focus was used as a seed region for functional connectivity analysis in the three conditions. A significant change in functional connectivity patterns was observed before the appearance of electrographic spikes. Specifically, there was significant loss of coherence between both hippocampi during the pre-spike period compared to spike and rest states. Conclusion/significance: In keeping with previous findings of abnormal inter-hemispheric hippocampal connectivity in MTLE, our findings specifically link reduced connectivity to the period immediately before spikes. This brief decoupling is consistent with a deficit in mutual (inter-hemispheric) hippocampal inhibition that may predispose to spike generation.